The Effect of Net Interest Margin (NIM) and Capital Adequacy Ratio (CAR) On Return on Assets (ROA) - Nadia Nurafida; Achmad Agus Yasin Fadli (Indonesian Development of Economics and Administration Journal, 2023)
This study aims to determine the effect of Net Interest Margin (NIM) and Capital Adequacy Ratio (CAR) on Return on Assets (ROA) at PT Bank Mandiri Tbk. The writing in this research uses a quantitative descriptive method. The type of data used is secondary data. The sample used in this study is the balance sheet and income statement of PT Bank Mandiri for the period 2013-2022. The results of the analysis show that 1) Partially, the independent variables do not have an influence on the dependent variable. 2) Simultaneously, no influence is found between the independent and dependent variables. Based on the determination calculation, an R Square value of 0.260 or 26% is obtained. This indicates that the percentage contribution of the independent variables, Net Interest Margin (NIM) and Capital Adequacy Ratio (CAR), to the dependent variable, Return on Assets (ROA), is 26%. The remaining 74% is influenced by other variables not included in this study.